2022
DOI: 10.1007/s40265-022-01782-4
|View full text |Cite
|
Sign up to set email alerts
|

Varenicline Solution Nasal Spray: A Review in Dry Eye Disease

Abstract: Increasing endogenous tear film production via pharmacological neuroactivation of the nasolacrimal reflex [NLR; also known as the trigeminal parasympathetic pathway (TPP)] is a novel therapeutic approach to treating dry eye disease (DED). An intranasal formulation of the water-soluble, small-molecule, nicotinic acetylcholine receptor (nAChR) agonist varenicline (Tyrvaya™) has been approved in the USA for the treatment of DED. Twice-daily administration of varenicline solution nasal spray resulted in rapid, sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 31 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…Topical cyclosporine and lifitegrast studies have reported that burning is the main ocular AEs with an overall compliance of 80.2% [45,55,59] and 91.1 [60][61][62], respectively. Varenicline nasal spray, which has recently been approved for DED treatment [63], seems to reduce the common AEs of topical ocular application modalities by achieving an overall compliance of 95.4% [64][65][66]. However, this systematic review has reported an overall compliance with REB ophthalmic suspension treatment of 96.8 ± 3.4%.…”
Section: Reb Ophthalmic Suspension Safetymentioning
confidence: 78%
“…Topical cyclosporine and lifitegrast studies have reported that burning is the main ocular AEs with an overall compliance of 80.2% [45,55,59] and 91.1 [60][61][62], respectively. Varenicline nasal spray, which has recently been approved for DED treatment [63], seems to reduce the common AEs of topical ocular application modalities by achieving an overall compliance of 95.4% [64][65][66]. However, this systematic review has reported an overall compliance with REB ophthalmic suspension treatment of 96.8 ± 3.4%.…”
Section: Reb Ophthalmic Suspension Safetymentioning
confidence: 78%
“…Overall, most of the adverse events are tolerable and lifitegrast can alleviate refractory DED and improves patients' quality of life [11]. The recently introduced varenicline, a nicotinic acetylcholine receptor agonist, is innovative in its route of administration [12]. Given as a nasal spray, varenicline acts rapidly and is effective and generally well tolerated, with its increase in endogenous tear secretion being a potentially useful advantage over existing therapies.…”
Section: Joj Ophthalmologymentioning
confidence: 99%
“…It is a nicotinic acetylcholine receptor agonist that binds to the nasociliary nerve within the nasal cavity. Four weeks of treatment saw improved results at week 12 [ 36 , 37 ]. Pharmacy-sponsored studies show significant improvement after 4 weeks of treatment and showed significantly better results compared to lifitegrast.…”
Section: Conventional Treatmentsmentioning
confidence: 99%